Mätning av träddelar och flis på Dåvamyran, Umeå energi - Hägg, Karin (2008)
The moisture content in 10 deliveries of tree parts and 10 deliveries of wood residues were measured with different methods to analyze the quality of procedure used at Dåvamyran today. At the same time a survey was made on the measure procedures used at heating plants in Sweden The majority of the heating plants in Sweden use weight and moisture content as base for payment but at some plants only volume. The moisture content is usually estimated by drying wood chips in an oven but few plants a visual estimation is used. At few plants moisture content is estimated spectroscopicily. The techniques using near infra read light and other electromagnetic are still at a test stage. The methods of measurement used today are quit unreliable for the individual deliveries and there is a risk for systematic mistakes. Ash content part varied with 5 % between the deliveries. Since the method for measuring ash content is statistical uncertain this parameter value for the parameter should be estimated by visuel inspection. Alternative procedures for Umeå Energy could be as follow: o Do not buy more tree parts than necessarily. o The price for tree parts should be more correctly. o Invest in equipment which makes it possible to estimate the moisture content in tree parts correctly such as camera technique and/or equipment to chip the material. Procedure for measuring wood chips is proposed to be: o The driver collects the wood chips samples. o The driver should walk around the stack after unloading. Collect four samples two litres, from four different locations. Two of the samples should be taken above and two samples should be taken below waist height. Estimate a value for ash content in the contracts and use this estimated value as base for payment. In the future when the new boiler is installed and the number of deliveries increases: o Use random samples of deliveries when estimating moisture content. o Use the Swedish wood measuring association (VMF) for neutral measurement. o Invest in NIR (Near Infra Read) equipment.